Phytoremediation of soil contaminated with zinc and lead by using Zea mays L. - Ahmed, Abdel-Haleem Mohammed; Latif, Hanan Helmy (Bangladesh Journal of Botany, 2018)
This study was carried out to investigate the potential of Corn (Zea mays) for phytoremediation of soil contaminated with lead (Pb) and zinc (Zn). The Zea mays L. cv. Giza 2, Hordeum vulgare cv. Giza 123 and Lupinus termis cv. Giza 1 species were planted in poted soil contaminated with lead and zinc. Zea mays was also cultivated with Hordeum and Lupinus treated with lead and zinc. The results showed that growth decreased by (16.7, 48.63 and 23.56%), photosynthetic pigments decreased by (10.18, 22.38 and 10.9%) and total-N decreased by (30.0, 27.27 and 13.64%) in Zea, Hordeum and Lupinus, respectively as compared to control. Proteins profile in shoots of tested plants revealed qualitative and quantitative changes. Co-cultivated Zea with Hordeum and Lupinus treated with lead and zinc improvement all parameters. The evidences provided by this experiment indicated that Corn acts as an effective accumulator to zinc and lead.